RUSSIAN POETIC SPEECH TODAY (Филологический класс, 2018)
The article analyzes the collection of poetry texts, included in the recently published volume «Russian Poetic Speech — 2016. An Anthology of Anonymous Texts». The anonymity factor (the 115 poets of various generations, living in Russia and abroad, who contributed to the volume, were not named) certainly contributes to the discovery of common features in Russian poetic speech of the late modernity. One of the main goals of the research was to perform categorical interpretation of the poems comprising the volume as one super-text. This method allowed for discovery of the poetic value of the individual geographies of the authors, as well as for cataloguing the meaning behind the verbal designators of space and time in poetry. The method also permitted to establish the principles behind the philosophic interpretation of time in its dynamics, to give overall assessment of the chronotope in its connections and relations to the image of a Collective Author, and to rethink the worldview of collective contemporary poet as the carrier of Russian language and the heir to the cultural and literary traditions of the nation. Isolating differential features of the concept of ‘poetic’ led to the discovery of the representational means for the super-text of ‘elevated’, ‘non-earthly’, and ‘sincere’. The article also analyzes the means for realization of the emotional and influential functions of the super-text, which particularly accompanies the through motive of linguistic and axiological resistance. Treading upon the Russian Formalist school dichotomy between the practical and the poetical language, the research determines the vector for aesthetic function of properly poetic texts as opposed to the texts of ‘applied’ poetry. We explored and described meaningful heuristic results of poetic speech creation: the unexpected parallels behind the mass of comparative tropes, as well as semantic approximation of words, included in the actual process of paronymic attraction. We have noted that the linguo-heuristic feature of contemporary poetic speech is less apparent in neologisms with affix genesis. The article outlines emerging unconventional tendencies, connected to orthographic, punctuational and graphic aspects of a poetic text.